Secondary Students’ Digital Literacy Skills in Accessing Online Information for English Language Learning: What Skill is? - Ummah, Nasihatul; Oktaviana, Fadilla; Perdana, Purnama Rika (Linguistics and ELT Journal, 2025)
The term ‘digital literacy’ has emerged because of the rapid development in technology (Liu et al., 2020). As we have seen, one reason is that technology has improved a lot, making a wide range of digital tools and platforms easy for both teachers and students to access (Hamilton, 2022). In this study, the author aims to explore secondary students’ digital literacy skills in accessing online information for supporting their independent learning. The method that conducted on this study is qualitative systematic review framework from Xiao & Watson (2019). To support the data, the author distributed the questionnaire via Google Form to fifteen secondary students of Senior High School. As a whole, the three of previous studies suggested that technology has a lot of potential to improve how students learn. Besides, on the result of supporting data showed that the students competent in accessing the internet to gain the online information for supporting their English language learning independently. To sum up, the focus learning area of English that improved is reading ability (41.2%) and speaking ability (29.4%).